Bioactivity study and chromatographic analysis of the extracts from nannochloropsis sp. Jacqui Lou B. Valenzuela. - Valenzuela, Jacqui Lou B. (2002.)
Nannochloropsis sp. is one of the marine phytoplankton that is considered the primary source of products having antibactrial activity and other products that are of great commercial importance., Based on the results of Phytoplankton Screening, Nannochloropsis sp. contains no alkaloids, saponins, anthraquinones and leucoanthocyanins; however, it contains tannins and flavonoids. Brine Shrimp Toxicity Assay showed that the crude methanolic extract and the four fractions obtained from liquid-liquid extraction were not toxic. Of the four fractions obtained, n-Hexane fraction has the lowest LC50 value while the DCM fraction has the hihgest LC50 value. The results of the Antimicrobial Assay did confirm that Nannochloropsis sp. has an antimicrobial property because it successfully inhibited the growth of V. harveyi, V. anguillarium, and B. subtilis. The species has a great potential as a source of antural product for antibiotic development. It can be used as component of probotics, thus serving as food for aquaculture species. It can also provide favorable environment as well as means of protection for them, By TLC analysis, it was found out that cardiac glycosides, phenolics, terpenes and flavonoids may be present in the crude methanolic and ethyl acetate fractions. Cardiac glycosides, phenolics and terpenes may be present in the aqueous fraction. Cardiac glucosides and phenolcis may be present in the DCM fraction. Cardiac glycosides and terpenes may be present in the n-Hexane fraction.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Nannochloropsis sp. -- Extracts